Uji Aktivitas Antidiabetes Kombinasi Ekstrak Etanol Daun Ciplukan (Physalis Angulata L. ) dan Madu Hutan Terhadap Mencit Putih Jantan yang Diinduksi Streptozotocin - Azizah, Masayu; Martha, Septiani; Agustina, Citra (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Research has been conducted on the test of antidiabetic activity in combination of ciplukan leaf ethanol extract (Physalis angulata L.) and Forest honey against white squeak male DM type-2. Test animals are made into mice dm type-2 models with streptozotocin induction diabetes test method. The study used 5 treatment groups, i.e. tween 80 as negative control, metformin 65 mg/kgBB as a comparison, combination of ciplukan leaf extract and forest honey EDCMH 35 mg/kgBB and 0.7 g/kgBB, combination of EDCMH 70 mg/kgBB and 0.7 g/kgBB, and EDCMH combination group 105 mg/kgBB and 0.7 g/kgBB. perorally with one-time daily administration for 7 days. The result of % decrease on the 7th day of the combined treatment group EDCMH 35 mg/kgBB and 0.7 g/kgBB, combination of EDCMH 70 mg/kgBB and 0.7 g/kgBB, and the combination group of EDCMH 105 mg/kgBB and 0.7 g/kgBB respectively was 32.28%, 36.44%, 44.06%. The data obtained was analyzed statistically with the Anova One Way and Pos Hoc tests. In this study it was known that the combination group of EDCM 105 mg/kgBB and 0.7 g/kgBB was the same as the metformin group as a comparison. The effective combination dose in reducing fasting blood sugar levels is combination of EDCMH 35 mg/kgBB and 0,7 g/kgBB.